A gastrointestinal stromal tumour with pulmonary metastases mimicking unilateral gynaecomastia. (16th December 2013) - Guler Cimen, Sanem; MacDonald, Frank; Cimen, Sertac; Molinari, Michele
Abstract : Gastrointestinal stromal tumours (GISTs) represent 1% of primary gastrointestinal cancers. These neoplasms most frequently metastasise to the liver and peritoneum and rarely to the lungs and bones. Treatment of unresectable GISTs involves systemic chemotherapy with tyrosine kinase inhibitors, imatinib and sunitinib being first-line and second-line drugs. We report the case of a 52-year-old man with GIST who developed a right-sided subareolar breast swelling and subsequently discovered to be an invasive metastatic pulmonary GIST. Given that gynaecomastia is a known adverse effect of imatinib and sunitinib, this case report illustrates the importance of including metastatic disease in the differential diagnosis of patients with GIST and with the new onset of soft tissue masses.